PENGARUH METODE TRANSLASI MATA UANG TERHADAP LABA KONSOLIDASI PT. GOTO GOJEK TOKOPEDIA TBK: PERBANDINGAN ANTARA PSAK DAN IFRS - M. Masrukhan; Alya Aulia Kusnandar; Gilang Jamaludin (Cahaya Ilmu Bangsa, 2024)
This study discusses the effect of currency translation methods on consolidated profit of PT. GoTo Gojek Tokopedia Tbk, by comparing the application of PSAK (Financial Accounting Standards Statement) and IFRS (International Financial Reporting Standards). Fluctuations in foreign exchange rates can affect a company's financial results, especially for companies operating in various countries. PSAK and IFRS have different ways of regulating currency translation, with IFRS providing more detailed and transparent regulations. The results of the study indicate that IFRS provides clearer disclosure of the impact of currency fluctuations on consolidated profit, which is important for understanding the company's financial condition. This study emphasizes the importance of choosing the right accounting standards to produce accurate financial statements.